Supper Club / Lara Williams. - Williams, Lara (Writer of Treats) (Hamish Hamilton, 2019)
Devastatingly perceptive, savagely funny and wildly original - the essential coming-of-age story for our times. With the deadpan wit of Fleabag and ruthless insight of Cat Person, Lara Williams tells a tale of rage and joy, hunger and friendship, bodies and the space they take up in the world. Twenty-nine year old Roberta has spent her whole life hungry - until the day she invents Supper Club. Supper Club is a secret society for hungry women. Women who are sick of bad men and bad sex, of hinted expectations to talk less, take less, be less. So they gather after dark and feast until they are sick. They drink and dance and roar. And, month by month, their bodies expand. At the centre of the Supper Club stands Roberta - cynical yet anxious, precocious and lost. She is seeking the answer to a simple question: if you feed a starving woman, what will she grow into?